A polarization propagation mechanism of Fe and Cu atoms co-doped in two-dimensional-Si3N4. (10th August 2020) - Li, Weili; Yan, Zhengxin; Zhai, Xiaowei; Chen, Li; Liu, Wei; Wang, Yixian; Zhou, Gaoliang; Xiong, Kezhao
Abstract : Fe and Cu atoms doped into two dimensional (2D) Si3 N4 honeycomb structures exhibit magnetic anisotropy, and planar spin-polarization propagation. Abstract : Extraordinary electron-spin polarization, magnetic anisotropy, and d electron location arise from strong correlation effects induced by Fe and Cu atoms doped into two dimensional (2D) Si3 N4 honeycomb structures. When an Fe atom is embedded to replace a Si atom, the emergence of intricate transport phenomena can be shown, such as the presence of an energy band structure, magnetic anisotropy, and spin-polarization propagation. Here, we investigated electronic structures with strong correlation effects using first-principles calculations. Spin data revealed that Fe preferentially selected the nearest-neighbour N atom to establish the spin-polarization propagation direction. Cu positioned in a next-near neighbour site increased the spin order and d electron location. We proposed the use of spin-polarization to examine special magnetic anisotropy in 2D wide energy bandgap materials.